(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article provides a comprehensive analysis of the institutional system of migration management in the Kyrgyz Republic, identifies key challenges and coordination mechanisms between government authorities, international organizations and civil society institutions. The functions and powers of relevant government agencies are considered - the Ministry of Labor, Social Security and Migration, the Ministry of Internal Affairs of the Kyrgyz Republic and the Ministry of Foreign Affairs of the Kyrgyz Republic, the State Committee for National Security of the Kyrgyz Republic, the Ministry of Digital Development of the Kyrgyz Republic and the National Statistical Committee of the Kyrgyz Republic. Special attention is paid to the analysis of the regulatory framework, including the Concept of Migration Policy of the Kyrgyz Republic for 2021-2030, resolutions of the Cabinet of Ministers of the Kyrgyz Republic and decrees of the President of the Kyrgyz Republic aimed at improving interdepartmental cooperation. The paper reveals the role of digital tools such as the Unified System of Accounting for External Migration and the migrant portal.kg, in increasing the transparency and efficiency of migration administration. The importance of international cooperation (IOM, UNICEF, the EAEU, the Almaty process) and the activities of the Coordinating Council on Migration Issues is shown. Based on the analysis, measures are proposed for institutional strengthening and digital transformation of migration management, strengthening interdepartmental coherence and developing mechanisms for diaspora participation in the socio-economic development of the country.